2004
DOI: 10.1111/j.1365-2249.2004.02449.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular responses and cytokine production in post-treatment hookworm patients from an endemic area in Brazil

Abstract: SUMMARYHuman hookworm infections are distributed widely in tropical areas and have a significant impact on host morbidity and human health. In the present study, we investigated the cellular responsiveness and cytokine production in peripheral blood mononuclear cells (PBMC) from Necator americanus-infected schoolchildren who had recently received chemotherapy, and compared them with non-infected endemic controls. Hookworm patients and treated, egg-negative individuals showed a lower cellular reactivity against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(128 citation statements)
references
References 37 publications
6
119
1
2
Order By: Relevance
“…Our studies demonstrated that neither the presence of IL-10 nor that of TGF-␤ altered the capacity of NK cells from egg-negative individuals to bind ES products, suggesting that these cytokines have little impact on receptors for NKBP interaction. These observations are further supported by the findings of Geiger et al (15,16), showing that high levels of IL-10 are present in all individuals resident in areas of hookworm endemicity. Despite the presence of elevated IL-10 in egg-negative individuals from areas of endemicity, their NK cells were clearly not affected in their capacity to interact with Necator ES products (Fig.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our studies demonstrated that neither the presence of IL-10 nor that of TGF-␤ altered the capacity of NK cells from egg-negative individuals to bind ES products, suggesting that these cytokines have little impact on receptors for NKBP interaction. These observations are further supported by the findings of Geiger et al (15,16), showing that high levels of IL-10 are present in all individuals resident in areas of hookworm endemicity. Despite the presence of elevated IL-10 in egg-negative individuals from areas of endemicity, their NK cells were clearly not affected in their capacity to interact with Necator ES products (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…The second mechanism that we considered to explain the impaired interaction of ES products with NK cells from Necator-infected individuals was the presence of IL-10, a well-established immunomodulator during chronic helminth infections (4,27). As reported by Geiger et al (15,16), IL-10 is highly elevated in individuals resident in areas of Necator transmission. To determine whether IL-10 might have the capacity to affect receptors important for binding of NK cells to ES products, we conducted in vitro binding experiments in which NK cells from egg-negative individuals were incubated for up to 72 h with different doses of IL-10 (1 to 125 ng/ml) prior to interaction with bioES.…”
Section: Cd3mentioning
confidence: 90%
See 1 more Smart Citation
“…+ regulatory T cells [23] and repeated infection with hookworm stimulates production of high levels of IL-10 [24], which inhibits host protective immunity against M. tuberculosis. Accordingly, there is a possibility that hookworm-induced IL-10 impacts on the sensibility to M. tuberculosis infection.…”
Section: Il-10mentioning
confidence: 99%
“…Children living in endemic areas of Brazil and who appear to be resistant to hookworm infection produce greater levels of both type-1 (IFN-c) and type-2 cytokines compared with chronically infected children (20), and a treatment study of infected adults from a highly endemic area of Papua New Guinea provided evidence that resistance to reinfection following treatment was associated with the type-2 cytokine, IL-5 (21). Together these data indicate a potential role for both type-1 and type-2 cytokinemediated mechanisms in protective immunity.…”
Section: Hookwormmentioning
confidence: 99%